Pembuatan Biodiesel Dari Biji Karet - I Wayan Susila, (Teknika, 2008)
Biodiesel from rubber seed oil (Hevea Brasiliensis) can be produced through double-stage transesterification processes, and the objectives of this research are to know the effect of reactant amount and reaction time on producing biodiesel from rubber seed oil. The method of this research is started by preparation process and oil extraction. The next step is degummed rubber seed oil. Continued with esterification with acid catalyst (H2SO4) 0.5% weight from rubber seed oil used, reactants are rubber seed oil and methanol with molar ratio 1:5, 1:6, 1:7 dan 1:9 at 50°C for 150 minutes with blending at hot strirrer scale 7. The processes are continued with transesterification process with base catalyst (NaOH) 0.5% weight from rubber seed oil used, reactants are rubber seed oil and methanol with molar ratio 1:9 at 50°C for 20, 30, 40 and 50 minutes with blending at hot strirrer scale 7. The last steps of these processes are yield and quality of biodiesel analysis. The result of this research shows that the maximum biodiesel yield of  94.871% can be obtained at molar ratio esterification process 1:6 and reaction time of transesterification process 40 minutes; density, kinematic viscosity, flash point and calculated cetane index are 0.877 g/cm3, 4.552 cSt, 103oC and 43.756 resvectively.